2016
DOI: 10.1016/j.ympev.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing next-generation sequencing to resolve the backbone of the Core Goodeniaceae and inform future taxonomic and floral form studies

Abstract: Though considerable progress has been made in inferring phylogenetic relationships of many plant lineages, deep unresolved nodes remain a common problem that can impact downstream efforts, including taxonomic decision-making and character reconstruction. The Core Goodeniaceae is a group affected by this issue: data from the plastid regions trnL-trnF and matK have been insufficient to generate adequate support at key nodes along the backbone of the phylogeny. We performed genome skimming for 24 taxa representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mandel et al, 2015Mandel et al, , 2017Goodeniaceae, Gardner et al, 2016;Columbiforms, Soares et al, 2016;Vitales, Zhang et al, 2016, Wen et al, 2018Eupolypod II Ferns, Wei et al, 2017;Hippeastreae, García et al, 2017;Protea, Mitchell et al, 2017). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, 2009;Moore et al, 2010;Nabholz et al, 2010;Xi et al, 2012;Guschanski et al, 2013;Straub et al, 2014;Mandel et al, 2015Mandel et al, , 2017Gardner et al, 2016;Sass et al, 2016;Soares et al, 2016;Zhang et al, 2016;García et al, 2017;Mitchell et al, 2017) or non-fully resolved trees (Willerslev et al, 2009;Barrett et al, 2013Barrett et al, , 2014Ma et al, 2014;Wei et al, 2017).…”
Section: Deep Radiation Of the Asian Palmate Araliaceaementioning
confidence: 99%
“…Nonetheless, an expanded full plastome data set along with the more abundant Sanger-based sequences available, could be coupled in future studies. A hybrid NGS and Sanger sequencing approach has been employed for other groups (Xi et al, 2012; Leaché et al, 2014; Gardner et al, 2016), and could help clarifying the backbone of a comprehensive Melastomataceae phylogeny. Recalcitrant phylogenetic backbones are a widespread and challenging phenomenon in angiosperms (Xi et al, 2012; Straub et al, 2014), and their resolution is critical to increase the confidence of ancestral state reconstructions, historical biogeographical scenarios and other evolutionary hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…While these markers have shown to be potentially able to resolve some clades, some relationships are still lacking support (Nyffeler 2002;Griffiths & Porter 2009;Hernández-Hernández et al 2011;Bárcenas et al 2011). In this case, nextgeneration sequencing (NGS) could be a useful tool, since it has transformed the study of nonmodel plant taxa in phylogenetic inferences with high throughput data allowing deep resolutions across major plant clades (Xi et al 2012;Ma et al 2014;Gardner et al 2016;Zong et al 2019). NGS data are also showing to be extremely useful for discovering informative regions across genomes, for marker development (Wu et al 2010;Dong et al 2012;Ripma et al 2014;Reginato et al 2016), as well as to investigate chloroplast genome evolution (Dong et al 2013;Mower & Vickrey 2018;Yao et al 2019).…”
Section: Introductionmentioning
confidence: 99%